MUSIK GEREJA DAN PENGARUHNYA TERHADAP RELIGIUSITAS JEMAAT UMAT KRISTEN GEREJA KRISTEN JAWI WETAN GEDANGAN KANDANGAN 2022-2023 - Princess Sulthana Sahira; Asep Awaludin (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study aims to describe the influence of church music on the religiosity of Christians in their lives as religious people and its relationship with human psychology. From there, the researchers analyzed the impact of church music on the religiosity of Christians in the Jawi Wetan Gedangan Christian Church. This study uses a psychological approach to the type of field research (grounded research). The research method used in discussing and researching this research is the descriptive method of qualitative analysis. A descriptive analysis method was used to describe the form of accompaniment music used by the Jawi Wetan Gedangan Christian Church and to analyze the influence of the congregation who attended the service. I found that church music is an essential element in worship in the Church, a complement to worship that can deepen the congregation's appreciation during prayer. The music used during worship can affect the congregation's enthusiasm to attend Church. Music creates a feeling of longing for church. The music playing can provoke the congregation's emotions so that they can express the contents of the heart that the people want to pour out to their Lord, and in this way, the feelings that are carried when entering the Church can be released and relieved.